Aberrant Forkhead Box O1 Function Is Associated with Impaired Hepatic Metabolism - Qu, Shen (2006)
FoxO1 plays an important role in mediating the effect of insulin on hepatic metabolism. Increased FoxO1 activity is associated with reduced ability of insulin to regulate hepatic glucose production. However, the underlying mechanism and physiology remain unknown. We studied the effect of FoxO1 on the ability of insulin to regulate hepatic metabolism in normal vs. insulin-resistant liver under fed and fasting conditions. FoxO1 gain of function, as a result of adenovirus-mediated or transgenic expression, augmented hepatic gluconeogenesis, accompanied by decreased glycogen content and increased fat deposition in liver. Mice with excessive FoxO1 activity exhibited impaired glucose tolerance. Conversely, FoxO1 loss of function, caused by hepatic production of its dominant-negative variant, suppressed hepatic gluconeogenesis, resulting in enhanced glucose disposal and improved insulin sensitivity in db/db mice. FoxO1 expression becomes deregulated, culminating in increased nuclear localization and accounting for its increased transcription activity in livers of both high fat-induced obese mice and diabetic db/db mice. Increased FoxO1 activity resulted in up-regulation of hepatic peroxisome proliferator-activated receptor-γ coactivator-1β, fatty acid synthase, and acetyl CoA carboxylase expression, accounting for increased hepatic fat infiltration. These data indicate that hepatic FoxO1 deregulation impairs the ability of insulin to regulate hepatic metabolism, contributing to the development of hepatic steatosis and abnormal metabolism in diabetes.